Ultra long infrared metamaterial absorber with high absorption and broad band based on nano cross surrounding. (February 2023) - Liang, Shiri; Xu, Feng; Yang, Hua; Cheng, Shubo; Yang, Wenxing; Yi, Zao; Song, Qianjv; Wu, Pinghui; Chen, Jing; Tang, Chaojun
Graphical abstract: We propose a broad band and high absorption adjustable ideal absorber. The whole structure is Cr-Ge-Si3 N4 -Ti from bottom to top. The simulation results show that three resonant absorption modes are generated at 9.15 μm, 10.68 μm and 15.17 μm, with absorption rates of 92.1%, 97.3% and 95.2%, respectively. The bandwidth of the absorber is broadened by adding a lossy dielectric layer. Then, the control variables of the structural geometry parameters of the absorber were studied respectively to obtain the best optimization parameters. Since then, comparisons of different underlying microstructures have confirmed the uniqueness of our structure. Finally, we simulate the absorption of the absorber in different polarization modes with varying incident angles. In addition, the performance of previous work and our absorber are compared. These studies show that our absorber has active tunability, polarization and incident angle sensitivity, and high absorption bandwidth. Highlights: The results of FDTD theory show that the absorber based on MDM structure has high absorption bandwidth and three resonant absorption peaks in the mid-infrared band, which indicates that the absorber has wavelength selectivity. By tuning the geometric parameters of the absorber structure, the active tuning of the absorber in a wide range is realized. The absorption of the absorber under the change of incident angle and polarization mode is simulated, and it is determined that the absorber is insensitive to polarization and incident angle. By adding a lossy dielectric layer, the bandwidth of the absorber can be broaded. Abstract: Long wavelength infrared (LWIR) wideband absorption is an important target in the research of middle infrared band. In this work, we study the absorption characteristics of Cr-Ge-Si3 N4 -Ti metamaterial absorber based on nanowire cross surrounding. The absorber has polarization independence when the light wave is incident vertically. Due to the coupling of surface plasmon resonance and the intrinsic absorption of lossy material, the numerical simulation calculation shows that the bandwidth with absorptivity greater than 90 % reaches 7.23 μm, and the average absorptivity in the LWIR band (8.98–16.21 μm) is 94.1 %. The absorption spectrum can be adjusted independently by changing the geometric parameters of the structure. Moreover, the absorber has excellent incident angle insensitivity in TE and TM modes. The designed absorber is simple in structure, easy to configure, and suitable for infrared imaging, thermoelectronic devices and thermal detection applications.